MO648SERUM SOLUBLE UROKINASE PLASMINOGEN ACTIVATOR RECEPTOR IN PATIENTS WITH DIABETIC KIDNEY DISEASE. (29th May 2021) - Lupusoru, Gabriela Elena; Ailincai, Ioana-Georgiana; Sorohan, Bogdan Marian; Andronesi, Andreea Gabriella; Lupusoru, Mircea; Andronesi, Danut; Manda, Dana; Caragheorgheopol, Andra; Ismail, Gener
Abstract: Background and Aims: Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease worldwide, associated with significant cardiovascular morbidity and mortality. Soluble urokinase plasminogen activator receptor (suPAR) is a novel biomarker associated with inflammation, endothelial dysfunction and kidney disease. There is a lack of studies that investigate the role of suPAR in patients with DKD. Our aim was to assess the level of serum suPAR and to evaluate its association with kidney function, proteinuria and histological lesions in patients with DKD. Method: We performed a cross-sectional study on 75 patients with DKD evaluated in our department between 2019 and 2020. Inclusion criteria were: age> 18 years, diagnosis of type 1 or type 2 diabetes mellitus, DKD and absence of malignancy, autoimmune disease, infectious disease and liver disease. Demographical, clinical and laboratory parameters were collected at the time of admission. A subset analysis was performed on 28 patients with biopsy- proven diabetic nephropathy (DN) to investigate the association of serum suPAR with histological lesions. Kidney function was evaluated based on serum creatinine and estimated with CKD-EPI formula, proteinuria was reported as 24h proteinuria and albumin/creatinine ratio (ACR) and serum suPAR levels were measured with a solid-phase ELISA kit. The detection range of the kit was 12 ‐360 pg/ml (7.8- 500). Results: Among the 75 patients, mean age was 57.9±12.2 years, male was the dominant gender (65.3%), mean BMI was 30.7±5.5 kg/m 2, most patients had hypertension (97.3%) and 22.7% were active smokers. Sixty six out of 75 patients (88%) had type 2 diabetes and the median duration of diabetes was 180 months (120- 240). Median values of estimated glomerular filtration rate (eGFR), 24h proteinuria and ACR were 24.3 ml/min (15- 36), 4.8 g/24h (1.9- 7.1) and 2000 mg/g, respectively. Median serum level of suPAR at the time of evaluation was 2857.2 pg/ml (1916.4- 3700.1). Its level was positively correlated with duration of diabetes (r= 0.278, p= 0.01), eGFR (r= 0.634, p< 0.001), 24h proteinuria (r= 0.490, p< 0.001), ACR (r= 0.524, p< 0.001) and negatively correlated with urine specific gravity (r= -0.284, p= 0.01). In the subset analysis on 28 patients with biopsy-proven DN, median suPAR level was 2474 pg/ml (1782-3745) and was positively correlated with DN class (r= 0.493, p=0.008) and interstitial fibrosis and tubular atrophy (IFTA) score (r= 506, p=0.006), but not with interstitial inflammation, arteriolar hyalinosis or arteriolosclerosis. Conclusion: Our study showed a high serum level of suPAR in patients with DKD and its association with duration of diabetes, urinary specific gravity, kidney function and proteinuria. We also found a positive correlation with severity of glomerular lesions and IFTA.